A Case Report on Bupivacaine Induced Limb Weakness; Type I Augmented Adverse Drug Reaction (ADR) - John, Jeffin Gloria (Journal of Pharmacy Practice and Community Medicine)
Bupivacaine is an amide-type, long-acting local anesthetic. It acts by preventing generation or conduction of nerve impulses by reducing sodium permeability and increasing action potential threshold. Lower limb motor weakness is a well-known complication of epidural analgesia with local anesthetics. In this case report a 60yr old female developed Bupivacaine induced lower limb weakness post-surgery. This event was identified as Type 1 augmented ADR which was assessed and reported with the help of Naranjo ADR scale. The dose of Bupivacaine was reduced as per clinical pharmacist’s suggestion and that helped in recovery from the weakness on the same day. Type 1 augmented ADR is related to the pharmacological action of the drug or due to the exaggerated pharmacologic response.
Keywords: Bupivacaine; Epidural analgesic; ADR; Limb weakness; Naranjo scale